Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1051/0004-6361/201220680
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of B-type asteroids from WISE data

Abstract: Aims. Our aim is to obtain more information about the physical nature of B-type asteroids and extend previous work by studying their physical properties as derived from fitting an asteroid thermal model to their NASA's Wide-field Infrared Survey Explorer (WISE) data. We also examine the Pallas collisional family, a B-type family with a moderately high albedo in contrast to the large majority of B-types. Methods. We applied a combination of the near-Earth asteroid thermal model and a model of the reflected sunl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
6
39
0
Order By: Relevance
“…1-3, and 7), including asteroids with blue/neutral and moderately red spectra (relative to the Sun). Our findings are consistent with, and complement previous spectroscopic studies that hinted at spectral diversity within the Themis family in the visible (Florczak et al 1999;Kaluna et al, 2016), the near-infrared (Ziffer et al 2011;de León et al 2012;Alí-Lagoa et al 2013), and the mid-infrared ). On the other hand, the robust and younger Beagle family members look different, with a smaller spectral slope variability.…”
Section: Spectral Slopes and Physical Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…1-3, and 7), including asteroids with blue/neutral and moderately red spectra (relative to the Sun). Our findings are consistent with, and complement previous spectroscopic studies that hinted at spectral diversity within the Themis family in the visible (Florczak et al 1999;Kaluna et al, 2016), the near-infrared (Ziffer et al 2011;de León et al 2012;Alí-Lagoa et al 2013), and the mid-infrared ). On the other hand, the robust and younger Beagle family members look different, with a smaller spectral slope variability.…”
Section: Spectral Slopes and Physical Parameterssupporting
confidence: 92%
“…Alí- Lagoa et al (2013), in the analysis of B-type asteroids and p IR albedo, found that an absorption in the 3 µm region may be common on these bodies. Figure 11 confirms the huge spectral variability of Themis members, which have small to moderate albedo values (3-16%) and a P IR /p v ratio varying from ∼ 0.5 to 2.2.…”
Section: Spectral Slopes and Physical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because even though its visible-to-near-infrared spectrum suggests that EV 5 belongs to the C-complex (Reddy et al 2012) and is thus rich in carbonaceous materials, its geometric albedo of 0.12 ± 0.04 -derived from a diameter of 400 ± 50 m measured from radar observations by Busch et al (2011) -is slightly outside the limit of what has traditionally been considered primitive. This is also the case for (2) Pallas and the Pallas collisional family (see, for example, Alí-Lagoa et al 2013).…”
Section: Introductionmentioning
confidence: 63%
“…Consequently, if p IR can be determined, it can be used as a proxy for distinguishing between taxonomic types that otherwise have nearly identical visible albedos (Grav et al 2012a,b;Alí-Lagoa et al 2013;Masiero et al 2014). While the STM, FRM, and NEATM are useful tools for rapidly determining effective spherical diameter, p V , and p IR for large numbers of asteroids, they are of limited use for determining additional parameters such as emissivity and thermal inertia.…”
Section: Thermal Modelingmentioning
confidence: 99%